Identification of a novel RMST-ALK rearrangement in advanced lung adenocarcinoma and durable response to ceritinib: A case report - Li, Hui; Deng, Yixiao; Chen, Bin; Xiao, Yajie; Yang, Jie; Liu, Qionghui; Lin, Gengpeng (Frontiers in Oncology, 2022)
Next-generation sequencing technology has enabled the identification of fusion partners of anaplastic lymphoma kinase (ALK) in non-small cell lung cancer, and various ALK fusion partners have been confirmed. Here, a novel rhabdomyosarcoma 2-associated transcript (RMST)-ALK rearrangement was identified in an 80-year-old Chinese man with advanced lung adenocarcinoma. The patient was prescribed ceritinib and achieved a partial response, which has been sustained for more than 18 months. This is the first report of the RMST-ALK rearrangement, and we showed that a patient with lung adenocarcinoma carrying this rearrangement can benefit from ceritinib treatment; therefore, this is a significant finding in clinical practice.